Pendampingan Pengembangan Video Pembelajaran Berbasis Kontekstual pada Materi Sistem Persamaan Linear Dua Variabel (SPLDV) untuk Meningkatkan Kemampuan Literasi Matematis Peserta Didik - Asmaul Husnah; Fitriani Nur; A. Sriyanti; Sri Sulasteri; Lisnasari Andi Mattoliang (UM Metro, 2025)
The use of technology in learning is being optimized, one of which is the use of learning videos, to guide students to learn independently efficiently and effectively. Therefore, community service is carried out in the form of learning assistance using contextual-based learning videos which aim to facilitate the improvement of students' mathematical literacy skills. The use of digital media was chosen because it is easy to use by teachers and students. This assistance was carried out for class VIII students of MTsN Gowa. The method in this community service is to provide material about SPLDV which is contextually based by utilizing learning videos and providing mathematical literacy learning outcome tests. The results and impacts of this community service are in the form of increasing mathematical literacy results and student motivation in learning and helping teachers in making digital-based learning innovations, so that the learning process in the classroom is more innovative and creative. On the other hand, it is also able to provide teachers with the opportunity to improve the quality of learning by utilizing digital media in the form of learning videos.